RINOSINUSITIS KRONIK: DIAGNOSIS HINGGA PROGNOSIS - Ferium Trah Ismaya (Jurnal Medika Hutama, 2023)
The epithelium of the respiratory tract is the main point of interaction between living organisms and their environment. The epithelium of the respiratory tract plays an important role in the process of disease and disorders of the respiratory tract. One of the diseases that can occur due to damage to this epithelium is chronic rhinosinusitis (CRS). CRS is generally defined as a clinical condition in the form of persistent inflammation of the nasal mucosa and paranasal sinuses, which lasts for 12 weeks or more. CRS can occur due to abnormalities in host and environmental factors. In general, the diagnosis of CRS can be made based on the history, physical examination, and supporting examinations. There are 2 main modalities in the management of CSR, namely medical management and surgical intervention. Various complications can arise if not treated properly including orbital, endocranial, and bone complications. The prognosis of CRS is influenced by the accuracy and speed in the process of diagnosis and administration of treatment.